Improving the Economy of Tenggor Village through Catfish Cultivation Using the Biofloc Method - Hidayat; Nina Aini Mahbubah; Muhammad Zainur Ridlo; Rohmat; Ulil Aulia; Tajri (Journal Of Humanities Community Empowerment, 2025)
This Community Service Program was carried out in Tenggor Village with the aim of improving the productivity and efficiency of catfish farming through the application of the biofloc system. The biofloc method was selected for its ability to utilize microorganisms to convert organic waste into natural feed, thus reducing feed costs and maintaining water quality. The program was implemented using a participatory approach, involving stages of field surveys, socialization, technical training in biofloc pond construction, cultivation assistance, and evaluation for sustainability. The results show the successful construction of one biofloc pond with a capacity of 1,000–1,200 fish, an increase in community knowledge from 40% to 85%, faster growth rates with a survival rate of 90%, and operational feed cost efficiency of 20–30%. In addition to its economic benefits, the program strengthened community cooperation and improved entrepreneurial awareness. These outcomes indicate that the biofloc system has strong potential to be expanded as a model for sustainable local economic development based on aquaculture.